2016
DOI: 10.1186/s12889-016-3815-1
|View full text |Cite
|
Sign up to set email alerts
|

Trends in body image of adolescent females in metropolitan and non-metropolitan regions: a longitudinal study

Abstract: BackgroundBody dissatisfaction is associated with a range of adverse outcomes, including impaired psychological health, low physical activity and disordered eating. This longitudinal study used the Factors Influencing Transitions in Girls’ Active Leisure and Sport (FITGALS) dataset to examine trends in body image of adolescent females. Specifically, the study examined satisfaction with body size, physical appearance and dieting behaviour for two cohorts at transitional life phases in two geographic regions lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
2
20
0
2
Order By: Relevance
“…Resumo Este estudo teve como objetivo investigar se as atitudes em relação à insatisfação com o peso corporal (PC) estão associadas à saúde percebida e ao comprometimento do sono em uma amostra de base populacional de Adolescence is characterized by a period in which many changes occur, considering that the person undergoes many biological and psychosocial adjustments, such as alterations in body proportion and body image distortion 1,2 . As a consequence, an increase in the levels of stress and reduced sleep quality due to poor psychological status is observed [3][4][5][6] .…”
Section: Attitudes Towards Body Weight Dissatisfaction Associated Witmentioning
confidence: 99%
See 2 more Smart Citations
“…Resumo Este estudo teve como objetivo investigar se as atitudes em relação à insatisfação com o peso corporal (PC) estão associadas à saúde percebida e ao comprometimento do sono em uma amostra de base populacional de Adolescence is characterized by a period in which many changes occur, considering that the person undergoes many biological and psychosocial adjustments, such as alterations in body proportion and body image distortion 1,2 . As a consequence, an increase in the levels of stress and reduced sleep quality due to poor psychological status is observed [3][4][5][6] .…”
Section: Attitudes Towards Body Weight Dissatisfaction Associated Witmentioning
confidence: 99%
“…Psychological health-related difficulties have been observed in the literature as a consequence of the exposure to a set of psychological concerns, such as body dissatisfaction 7 . It is observed that adolescents experience high levels of dissatisfaction with body weight 1,8 , signaling important health risks for this population 9 .…”
Section: Attitudes Towards Body Weight Dissatisfaction Associated Witmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,4,5 Another study found that, over time, more girls consider themselves to be "too fat," with slightly more older girls than younger girls reporting feeling too fat (45.5% v 40.9%). 6 The study also found that girls increasingly dieted as they grew older. 6 Statistics like the above prompt us to wonder: How did we get here?…”
Section: Media Body Imagesmentioning
confidence: 83%
“…6 The study also found that girls increasingly dieted as they grew older. 6 Statistics like the above prompt us to wonder: How did we get here? Why do we have a global epidemic of poor body image among children as young as five years old?…”
Section: Media Body Imagesmentioning
confidence: 83%